Caracteristicas miofuncionais e eletromiográficas da motricidade orofacial de obesos - Berlese, Denise Bolzan (2012)
This study aimed to evaluate the myofunctional and electromyographic characteristics of Orofacial obese. The sample consisted of 28 obese, aged between 8 and 16 years of both sexes from groups of the Obesity Clinic of Pediatrics, University Hospital of Santa Maria. We used the Assessment Protocol Myofunctional with scores (AMIOFE) to evaluate myofunctional and electromyographic evaluation of masseter and temporal muscles was obtained using the Lynx Electromyograph and performed three collections for each of the situations (rest, chewing, swallowing and maximum intercuspation). The results showed that the appearance of the cheek and palate was normal in less than 50% of the obese, the symmetry of the face occurred in over 50% in women and children in language and was contained in the oral cavity more than 60% of obese. The chewing function was performed bilaterally alternating swallowing occurred with normal occlusion of the lips and efficiency complement the solid and liquid bolus occurred without repeating the same bolus for the most obese. As for the behavior of the tongue, 23% of boys and 27% of the girls had brought to the dental arches with adaptation or dysfunction. When the normalized mean of electric activity of masseter and temporal muscles during swallowing, chewing and rest it was observed that the male has a higher percentage of muscle activation for the functions of chewing, swallowing and rest in all muscles. By relating the muscle activity in masseter and temporal characteristics myofunctional observed that most subjects showed bilateral chewing and the average electrical activity of muscles was evaluated superior to using preferably unilateral chewing. During swallowing, the values of electrical activity were higher in the right temporal and masseter muscles when normal occlusion of the lips, and the left temporal muscle show greater activation in obese patients who had occlusion of the lips with effort. As for the behavior of the tongue when it was contained in the oral cavity the values of electrical activity were higher in relation to the tongue brought to the dental arches. According to the results of this research, we concluded that most of the subjects showed characteristic within the normal range, no statistically significant difference when compared by sex and age group. Regarding the percentage of the electrical activity of muscles tested there is a tendency to decrease in muscle activation in the evaluated situations. By relating the muscle activity of masseter and temporal with the myofunctional characteristics of chewing and swallowing functions was observed that, when these appropriate there is a greater muscle activation of the right temporal muscle, left and right masseter during chewing and swallowing.